2015
DOI: 10.1166/jmihi.2015.1645
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Osteoporosis by Extracting the Microarchitectural Properties of Trabecular Bone from DXA Scans Based on Thresholding Technique

Abstract: The purpose of this study was to find optimal thresholding conditions for diagnosing osteoporosis using a novel thresholding technique. Seven trabecular features-composed of four structural and two skeletonized features as well as the fractal dimension (FD)-were extracted from 2D DXA scans. A binarized image was used to identify the structural features and the FD, and the skeletonized feature sets were obtained from a skeletonized image. The proposed thresholding technique utilizes the percentages for the trab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A 2019 review article reported that recent developments in AI have led to successful applications aiding osteoporosis diagnosis [ 15 ]. The following modalities have been used: dental radiographs [ 16 , 17 ], spine radiographs [ 14 , 18 ], hand and wrist radiographs [ 19 , 20 , 21 , 22 ], DXA imaging [ 23 , 24 ], and spine computed tomography [ 25 , 26 ]. However, two reports are available on osteoporosis diagnosis from hip radiographs using machine learning [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2019 review article reported that recent developments in AI have led to successful applications aiding osteoporosis diagnosis [ 15 ]. The following modalities have been used: dental radiographs [ 16 , 17 ], spine radiographs [ 14 , 18 ], hand and wrist radiographs [ 19 , 20 , 21 , 22 ], DXA imaging [ 23 , 24 ], and spine computed tomography [ 25 , 26 ]. However, two reports are available on osteoporosis diagnosis from hip radiographs using machine learning [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not all of the image-based features are helpful for tissue characterization, and some may negatively influence the classification results [48, 49]. In order to reduce the dimensionalities and select optimum feature sets, principal component analysis (PCA) was implemented followed by a varimax rotation.…”
Section: Methodsmentioning
confidence: 99%